First-principles study of the morphology and surface structure of LaCoO3 and La0.5Sr0.5Fe0.5Co0.5O3 perovskites as air electrodes for solid oxide fuel cells. Issue 1 (1st January 2021) - Nakayama, Masanobu; Nishii, Katsuya; Watanabe, Kentaro; Tanibata, Naoto; Takeda, Hayami; Itoh, Takanori; Asaka, Toru
ABSTRACT: The slow kinetics of the oxygen exchange reaction at the surface of air electrodes for solid oxide fuel cells must be improved to reduce their operating temperature. In this study, we use first-principles computation, based on the density functional theory, to investigate the surface morphology and oxygen vacancy formation energies of perovskite-type LaCoO3 and La0.5 Sr0.5 Co0.5 Fe0.5 O3 (LSCF5555) compounds. The cationic arrangement is optimized energetically for LSCF5555 using a genetic algorithm approach. We confirm that Sr and Co condensation occurs near the LSCF5555 surface. Significant lowering of the oxygen vacancy formation energies at the perovskite surface is indicated for both the compounds. In addition, several surface O sites in LSCF5555 exhibit lower oxygen vacancy formation energies than those in LaCoO3, which may improve the kinetics of the surface charge-transfer reaction in the LSCF-related compounds. Graphical Abstract: uf0001